(untitled) - Obešlová, Miluše (Aura musica, 2013)
The paper deals with the tasks of voice training in the core curriculum for basic education and the outcome in the end stages of primary schooling. It deals with very general and incomplete definition of basic skills for physiologically correct use of spoken and singing voice and has concretized the expected outcomes for pupils fifth and ninth grades. Following the main tasks of voice training are analyzed songs from music textbooks in terms of their tonal range.
Keywords: vocal training; outcomes; textbooks music; songs